5=3(-5r+5)-5(2+5r)

Simple and best practice solution for 5=3(-5r+5)-5(2+5r) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5=3(-5r+5)-5(2+5r) equation:


Simplifying
5 = 3(-5r + 5) + -5(2 + 5r)

Reorder the terms:
5 = 3(5 + -5r) + -5(2 + 5r)
5 = (5 * 3 + -5r * 3) + -5(2 + 5r)
5 = (15 + -15r) + -5(2 + 5r)
5 = 15 + -15r + (2 * -5 + 5r * -5)
5 = 15 + -15r + (-10 + -25r)

Reorder the terms:
5 = 15 + -10 + -15r + -25r

Combine like terms: 15 + -10 = 5
5 = 5 + -15r + -25r

Combine like terms: -15r + -25r = -40r
5 = 5 + -40r

Add '-5' to each side of the equation.
5 + -5 = 5 + -5 + -40r

Combine like terms: 5 + -5 = 0
0 = 5 + -5 + -40r

Combine like terms: 5 + -5 = 0
0 = 0 + -40r
0 = -40r

Solving
0 = -40r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '40r' to each side of the equation.
0 + 40r = -40r + 40r
Remove the zero:
40r = -40r + 40r

Combine like terms: -40r + 40r = 0
40r = 0

Divide each side by '40'.
r = 0

Simplifying
r = 0

See similar equations:

| 7k+2=16 | | -8+1x=1x+4x | | 5x+7=2x-11 | | 4.3xp=28.81 | | -v/5+2=-3 | | 8x^7+16x^9-12x^4+28= | | 2x=42-4x | | 1/5x=-20 | | 3*2+b*7=-1 | | 3x*6=33 | | 3y-8x=2 | | 5x+202=14x-5 | | 8=-6x+32 | | 3*2+7=-1 | | 7x/12=7 | | ((12-4x)+(5-7x))/2=11.5 | | 2y-3x=7 | | 10x+6+6x+34= | | 8x^7+16x^8-12x^6+28= | | 2x+5x=x-4-8 | | ((11X+19)/(X+5))=(X+1) | | 139-2x=43x+24 | | Uw+z=v | | 2x^2-y^2=0 | | -2x+3=-6x | | 2/5x+y=3 | | 9-10x=174-45x | | 64-7x=2x+23 | | 6x-3=1+6x | | 6x+16=15x-92 | | 6-8x=18-15x | | ((10)/(x-5))+((10)/(x+5))=3 |

Equations solver categories